La experimentación con proyectos trasfronterizos en el periodismo multimedia: posibilidades, realidades y retos - López, Xosé (Estudios sobre el Mensaje Periodístico, 2003)
The journalism of 21st Century has to face the facts. Its roots, supported by their heritage, need fresh sap to overcome the new challenges which arrive with medium that are changing some paradigms of communication. This very moment looks propitious for the promotion of experiences for the application of new tools from the labs of the faculties of Communication Sciences. These tools are useful for the construction of messages, which are destined to the net of nets, the Internet. From an interregional initiative of a work group in Galicia and other in the North of Portugal, named Gacetadominho.org, we developed a reflection about the current scenery of communication and the possibilities provided by new media. The creation of this electronic newspaper, making use of the guidelines of the best journalism, showed us that it is possible the elaboration of quality information products.